Wound Healing Metabolites from Peters’ Elephant-Nose Fish Oil: An In Vivo Investigation Supported by In Vitro and In Silico Studies - Faisal Alsenani (MDPI AG, 2021)
Gnathonemuspetersii (F. Mormyridae) commonly known as Peters’ elephant-nose fish is a freshwater elephant fish native to West and Central African rivers. The present research aimed at metabolic profiling of its derived crude oil via GC-MS analysis. In addition, wound healing aptitude in adult male New Zealand Dutch strain albino rabbits along with isolated bioactive compounds in comparison with a commercial product (Mebo®). The molecular mechanism was studied through a number of in vitro investigations, i.e., radical scavenging and inhibition of COX enzymes, in addition to in silico molecular docking study. The results revealed a total of 35 identified (71.11%) compounds in the fish oil, belonging to fatty acids (59.57%), sterols (6.11%), and alkanes (5.43%). Phytochemical investigation of the crude oil afforded isolation of six compounds 1–6. Moreover, the crude oil showed significant in vitro hydrogen peroxide and superoxide radical scavenging activities. Furthermore, the crude oil along with one of its major components (compound 4) exhibited selective inhibitory activity towards COX-2 with IC50 values of 15.27 and 2.41 µM, respectively. Topical application of the crude oil on excision wounds showed a significant (p < 0.05) increase in the wound healing rate in comparison to the untreated and Mebo®-treated groups, where fish oil increased the TGF-β1 expression, down-regulated TNF-α, and IL-1β. Accordingly, Peters’ elephant-nose fish oil may be a potential alternative medication helping wound healing owing to its antioxidant and anti-inflammatory activities.